Predicting Gambling Situations: The Roles of Impulsivity, Substance Use, and Post-Traumatic Stress. (June 2019) - Grubbs, Joshua B; Chapman, Heather
Gambling disorder and symptoms of post-traumatic stress are highly comorbid. Numerous studies suggest that the presence of one (either disordered gambling or post-traumatic stress) substantially increases the odds of later developing the other. However, little is known about the etiological links between these two domains or the nuances of the comorbidity. Past research has suggested that symptoms of post-traumatic stress might be related to unique motivations for and beliefs about gambling. The present work sought to examine whether or not symptoms of post-traumatic stress might also be related to specific situational vulnerabilities to gambling behaviors. Using a large cross-sectional sample of Internet-using adults in the United States who were primarily recreational gamblers (N = 743; 46% men, Mage  = 36.0, SD = 11.1), as well as an inpatient sample of US Armed Forces veterans seeking treatment for gambling disorder (N = 332, 80% men, Mage  = 53.5, SD = 11.5), the present work tested whether or not symptoms of post-traumatic stress were uniquely related to a variety of gambling situations. Results in both samples revealed that even when controlling for potentially confounding variables (eg, substance use and trait impulsivity), symptoms of post-traumatic stress were uniquely related to gambling in response to negative affect, gambling in response to social pressure, and gambling due to a need for excitement. These findings are consistent with recent work suggesting that individuals with post-traumatic stress symptoms are more likely to engage in gambling behaviors for unique reasons that differ from gamblers without such symptoms.